Stress overload, influencing factors, and psychological experiences of nurse managers during early stages of the COVID-19 pandemic: a sequential explanatory mixed method study - Jin, Yundan; Cui, Feifei; Wang, Rongting; Chen, Shuainan; Hu, Lina; Yao, Meiqi; Wu, Haiying (Frontiers in Psychology, 2023)
Background Healthcare systems had an exceptionally difficult time during the early COVID-19 pandemic. Nurse managers in particular made enormous contributions to ensuring the safety of patients and front-line nurses while being under excessive psychological stress. However, little is known about their experiences during this time. Objective The aim of this study was thus to assess the level of stress overload and psychological feelings of nurse managers during the early COVID-19 pandemic. Methods A mixed methods sequential explanatory design study with non-random convenience sampling was performed, following the STROBE and COREQ checklists. The study was conducted at the Affiliated Dongyang Hospital, Wenzhou Medical University, with data collected from six provinces in southern China (Zhejiang, Hubei, Shanghai, Jiangsu, Hunan and Jiangxi) during March 2020 and June 2020. A total of 966 nurse managers completed the Stress Overload Scale and Work-Family Support Scale. In addition, a nested sample of nurse managers participated in semi-structured face-to-face interviews. The data were then analyzed using qualitative content analysis, Pearson correlation, and multiple linear regression. Results The quantitative results showed that nurse managers experienced a moderate level of stress load. There was a significant negative correlation between work-family support and stress load (r = −0.551, p < 0.01). Concerns about protecting front-line nurses and work-family support were the main factors affecting the stress load, which accounted for 34.0% of the total variation. Qualitative analysis identified four main thematic analyses that explained stress load: (1) great responsibility and great stress, (2) unprecedented stress-induced stress response, (3) invisible stress: the unknown was even more frightening, and (4) stress relief from love and support. Taken together these findings indicate that concern about protecting front-line nurses and negative work-family support of nurse managers were the main factors causing stress overload. Conclusion Implementing measures focused on individual psychological adjustment combined with community and family support and belongingness is one potential strategy to reduce psychological stress among nurse managers.